HUBUNGAN PANJANG TUNGKAI DAN POWER OTOT TUNGKAI TERHADAP PRESTASI LOMPAT JAUH PADA SISWA PUTRA SMP NEGERI 2 LABUHAN BADAS KABUPATEN SUMBAWA BESAR - Sukarman, Sukarman (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2021)
This study aims to determine the strength of leg length and leg muscle strength, which are very important components in order to improve the overall physical condition. The purpose of this study was to determine whether there was a relationship between leg length and leg muscle power on long jump achievement in male students of class VIII SMP Negeri 2 Labuhan Badas, Sumbawa Besar sub-district, academic year 2020/2021. The method used in this study was to use deed test method and documentation method. The action test method is carried out in accordance with a predetermined instrument, while the documentation method is used to strengthen the research. And the method for analyzing data uses multiple linear correlational methods. The results obtained are based on the results of data processing, namely the correlation value (r) is calculated = 0.108. And the results of the correlation (r) table = 0.44, then the meaning of the relationship between leg length and leg muscle power to long jump performance in male students of class VIII SMP Negeri 2 Labuhan Badas Kecangkas Sumbawa Besar, is not significant or there is no relationship, this can be seen from correlation norm.